Experimental investigation of the effect of using expanded polystyrene geofoam and geogrid in different forms on vertical earth pressure on high-filled cut-and-cover roadway tunnel - Mohammad Hajiazizi; Shamil Ahmed Flamarz Arkawazi (Cogent Engineering, 2024)
AbstractUsing high-filled cut-and-cover tunnels (HFCCTs) can provide a practical and ideal solution for the possibility of using highly demanded lands with plateaus terrain. The huge amount of HFCCT backfill soil produces ultrahigh vertical earth pressure (VEP). Therefore it is necessary to use load reduction methods and mechanisms to reduce the VEP on the HFCCT, which will reduce the risks and increase safety by reducing the tunnel designing loads. This experimental study describes methods of VEP reduction on the HFCCTs using expanded polystyrene (EPS) geofoam as a compressible material in two different forms without and with the presence of geogrid on top of the EPS. Several important factors, including the effect of geogrid presence on top of the EPS, the EPS form, the EPS thickness, and the distance between the bottom of the EPS and the top of the HFCCT discussed and studied. It determined from the study results that the mentioned factors have significant effects on the VEP reduction on the HFCCTs through their roles in the VEP reduction mechanisms. This study adopted two VEP reduction mechanisms; relative vertical displacements of the HFCCT backfill soil prisms and soil arching. The mentioned two mechanisms caused a significant reduction in the VEP on the top of the HFCCT, where the best result was a 76.0% reduction in the VEP on the HFCCT.